2019
DOI: 10.1111/jftr.12352
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Our Focus From Father Involvement to Father–Child Relationship Quality

Abstract: Most of the many existing ways to conceive and measure paternal relationships incorporate ways to gauge father involvement. Although father involvement is a well‐established, important component of studying fathering relationships, it offers a circumscribed understanding of key characteristics of father–child relationships and their quality. Synthesizing theoretical and empirical literature across broader indicators of father–child relationship quality (FCRQ) affords fuller consideration of developmental traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 81 publications
4
81
0
6
Order By: Relevance
“…2021, 11, 816 2 of 18 and in the phenotypes of fathering behavior [11]. Nonetheless, there is also a growing need and interest to understand the impact of a more prominent role for the paternal figure in the family caregiving environment on subsequent child development [12] and the neurobiological underpinnings of fatherhood [13][14][15]. The present study provides a review of functional magnetic resonance imaging (fMRI) studies conducted so far on the neurological correlates of fatherhood and paternal caregiving in humans with a specific focus on brain responses to infant-related stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…2021, 11, 816 2 of 18 and in the phenotypes of fathering behavior [11]. Nonetheless, there is also a growing need and interest to understand the impact of a more prominent role for the paternal figure in the family caregiving environment on subsequent child development [12] and the neurobiological underpinnings of fatherhood [13][14][15]. The present study provides a review of functional magnetic resonance imaging (fMRI) studies conducted so far on the neurological correlates of fatherhood and paternal caregiving in humans with a specific focus on brain responses to infant-related stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 'it is not so much the frequency of contact per se that matters for child well-being but, rather, the extent to which post-divorce residence arrangements reflect predivorce parenting arrangements' (Poortman 2018, p. 671). Apart from the sheer quantity of contact, qualitative aspects of the contact are also important, such as the quality of the father-child relationship, and how the father and child spend their time together (Palkovitz 2019). In addition to examining what makes parentchild relationships satisfying, research has identified the co-parental relationship as a key factor in children's well-being and adjustment levels after divorce (Amato 2000;Becher et al 2019).…”
Section: Custody and Contact After Parental Divorcementioning
confidence: 99%
“…As well, fathering has been studied as reflective of components of positive parenting practices (Baumrind, 1991), such as positive engagement activities, warmth and responsiveness, control, and process responsibility (Cabrera et al, 2018;Pleck, 2007). Palkovitz (2019) expanded the focus from fathers' behavior to include father-child relationship quality, which encompasses affect, behavior, and cognition. In other words, fathers and children build interdependent relationships based on mutual interactions, as well as the thoughts and feelings they have about each other.…”
Section: Fathering Researchmentioning
confidence: 99%
“…For fathers, the process of building a relationship through interactions with a child increases commitment to the fathering role, which impacts self-confidence, satisfaction, emotions, and decision-making (Pleck, 1997). From each interaction, fathers reflect on their performance (Palkovitz, 2019), garnering additional commitment to the role. Commitment to a role delineates how central that role is in one's life (Stryker, 1987), which consequently may affect his motivation to enact the behaviors that are appropriate for that role (Pasley et al, 2002).…”
Section: How Identity Influences Foster Fatheringmentioning
confidence: 99%